Water Productivity: Revisiting the Concepts in Light of Water, Energy and Food Nexus an Overview of Question 60, 23rd Congress of ICID†‡. (15th February 2019) - Debbarh, Abdelhafid
Abstract: The International Commission on Irrigation and Drainage (ICID) has organized its 23 rd International Congress in Mexico City during the period 08–‐14 October 2017. Its overall theme was: Modernizing Irrigation and Drainage for a new Green Revolution . Two Questions 60 and 61 were addressed and concerned respectively the following issues: Question 60 on Water Productivity: Revisiting the concepts in light of water, energy and food nexus, and Question 61 on State of knowledge of irrigation techniques and practicalities within given socio‐economic settings . The present paper aims at giving a summary of the main axis covered by the various contributions on Question 60. In fact, 91 contributions from 27 countries analyzed and discussed the three following sub themes related to Question 60, namely: i) Emerging issues and challenges of water saving, including impact of transferring water out of agriculture ; ii) Understanding water productivity, water and energy use efficiency and water footprint of crops ; iii) Water security for growth and development . A summary of the main ideas and findings emerged, for each sub theme mentioned above, are herein presented. Majors conclusions and recommendations are also included at the end of this paper. © 2019 John Wiley & Sons, Ltd.